Detection of double-stranded RNA in Mucor ramannianus - Ca Vágvölgyi; J. Varga; L. Ferenczy (Fungal Genetics Reports, 1993)
Double-stranded RNA (dsRNA) molecules have been found in numerous fungal species and are considered to be indicators of the presence of virus-like particles (VLPs) in the cells (Hollings 1978 Adv. Virus Res. 22:1-53; Buck ed., 1986 Fungal Virology, CRC Press, Boca Raton, FL). Such mycoviruses have been found mainly from studies of the nucleic acids of different strains. In this respect, fungal species belonging to the Zygomycetes are rarely screened. We have investigated the nucleic acids of 30 Mucor strains representing ten different species. The presence of dsRNA molecules was detected in only one of the two Mucor ramannianus strains examined.